Fibronectin urothelial gene expression as a new reliable biomarker for early detection of local toxicity secondary to adjuvant intravesical therapy for non-muscle invasive bladder cancer - Di Maida, Fabrizio (Ther Adv Urol, 2021)
BACKGROUND: A marker of urothelial damage could be helpful for early detection and monitoring of local toxicity due to intravesical therapy for non-muscle invasive bladder cancer (NMIBC). The aim of the study was to investigate the correlation between fibronectin (FN) gene expression in bladder washings and local toxicity secondary to adjuvant intravesical therapy. MATERIALS AND METHODS: Patients undergoing adjuvant intravesical therapy for NMIBC and age-matched healthy patients were enrolled. Real time polymerase chain reaction was performed to analyze FN expression in bladder washings. Local toxicity was classified as: 0–1 mild (no medical therapy), 2 moderate (medical therapy and/or instillation postponed), 3 severe (discontinuation of therapy). RESULTS: Seventy-two patients and 21 controls entered the study. A useful pellet was obtained in 58 patients and 18 controls. Intravesical Bacillus Calmette–Guerin (BCG), Epirubicin and Mitomycin C was offered to 69%, 13.8% and 17.2% of patients respectively. Compared with healthy controls (FN = 1.0 fold), overall median FN expression before adjuvant intravesical therapy was 1.73 fold [interquartile range (IQR) 0.8–2.3], while during therapy median FN expression increased to 3.41 (IQR: 1.6–6.1) fold. Considering 40 intermediate and high-risk patients undergoing intravesical BCG, median FN expression before adjuvant treatment was 1.92 [(IQR: 1.0–2.7) fold, increasing up to 4.1 (IQR: 1.9–6.6) during therapy. In more detail, FN increased during BCG therapy, showing a median expression of 4.22 (IQR: 2.2–5.5) and 6.16 (IQR: 2.6–8.7) fold in presence of grade 2 and 3 toxicity respectively, while remaining more or less stable in asymptomatic patients. After receiver operating characteristic curve analysis, FN value of 3.6 fold resulted, corresponding to 75% sensitivity and 69% specificity to predict grade 2–3 toxicity events (area under the curve 0.74, 95% confidence interval 0.63–0.85, p = 0.001). CONCLUSION: Our study validated the correlation between FN expression and urothelial damage. BCG seems to induce a urothelial activation with FN overexpression during adjuvant intravesical therapy. Grade of toxicity was related to FN expression.